Psikoedukasi untuk Menurunkan Perilaku Agresi pada Anak Usia Sekolah - Nurfatihah Dahlan; Nadya Alawwiyah; Cahyaning Suryaningrum; Yuni Nurhamida (CV. ITTC INDONESIA, 2026)
Aggressive behavior in school-age children is a problem that can hinder their development and create a less conducive learning environment. This community service program aims to reduce the tendency for aggressive behavior in school-age children and increase the understanding of volunteer teachers as a support system through a psychoeducational approach. Activities were conducted with school-age children and volunteer teachers using lectures, educational games, video screenings, case studies, role-plays, reflections, and tutorials on implementing reward systems. Evaluation was conducted using quantitative and qualitative approaches through pre- and post-tests, as well as observations during the activity. The analysis revealed a significant difference between pre- and post-test scores for both children and volunteer teachers, with a large effect size. Qualitative findings also demonstrated changes in children's responses to more adaptive emotional expression. Thus, psychoeducation involving children and volunteer teachers has proven effective in preventing and addressing aggressive behavior in community learning environments.